Did informed order flow move to multilateral trading facilities? Evidence for some Eurozone countries. Issue 2 (3rd April 2018) - Pereira da Silva, Paulo
ABSTRACT: This paper investigates the effects of the fragmentation of European stock markets after MiFID application in 2007. Specifically, we discuss whether the process of fragmentation elicited a flight of informed trading from the primary stock exchanges to the incoming multilateral trading facilities (MTFs). Our sample covers 438 stocks traded on six important markets of the Eurozone and the period ranging from 2010 to 2015. Our findings demonstrate that, on average, primary exchanges still drive the process of price formation. However, MTF platforms have been gradually expanding their influence over the price discovery process of some of the stocks so that for a non-negligible minority of them, MTFs already lead the price discovery.